Academic Women’s Labour During the COVID-19 Pandemic: A Review and Thematic Analysis of the Literature - De Giusti Bordignon, Mara; Viczko, Melody (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2024)
The COVID-19 pandemic has impacted academic labour, with women being disproportionately negatively affected. This scoping review provides an exploratory snapshot into the corpus of literature investigating the impact of the pandemic on academic labour. We used a set of criteria to first identify the 86 titles from which we selected 45 as the data set. We analyzed the data on characteristics of location, investigative methods, publication information, and discipline. The findings showed that most of the data were global in context; used primarily qualitative methodologies; published in a wide variety of journals; and spanned diverse disciplines, including science and health, education, business, sociology, and political sciences. We then analyzed the data thematically. The themes we identified were gender inequity, identities and intersectionality, performing work-home binaries, and invisible labour. We added a fifth theme, lived experiences, consisting of women academics’ firsthand accounts. We consider this theme unique, despite its overlap with the other themes, because it is evidence of women academics telling their personal stories. We discuss how our findings show that pandemic conditions worsened existing inequities. The solutions most often cited in the data place emphasis and responsibility on the individual, but we argue that institutions should instead be responsible to redress inequities through improving workplace labour processes. Our research can aid future research on how policy theory can inform socially just policies and practices in the post-pandemic university.